Substituted aziridines by lithiation-electrophile trapping of terminal aziridines. - Hodgson, D; Humphreys, P; Ward, J (2005)
[reaction: see text] Regio- and stereoselective deprotonation of N-Bus (Bus = tert-butylsulfonyl)-protected terminal aziridines with lithium 2,2,6,6-tetramethylpiperidide generates a nonstabilized (H-substituted) aziridinyl anion that undergoes in situ or external electrophile trapping under experimentally straightforward conditions to give trans-disubstituted aziridines in good to excellent yields.